Living with Debt : How Institutions Can Chart a Path to Recovery in Middle East and North Africa - Gatti, Roberta; Lederman, Daniel; Nguyen, Ha M.; Alturki, Sultan Abdulaziz; Fan, Rachel Yuting; Islam, Asif M.; Rojas, Claudio J. (Washington, DC: World Bank, 2021)
Economies in the Middle East and North Africa (MENA) remain in crisis. The World Bank estimates the regional output to have contracted 3.8 percent in 2020 and expects it to rebound by only 2.2 percent in 2021. The regional output is expected to be 7.2% below where it would be in 2021 without the pandemic. The region’s average GDP per capita is estimated to have declined 5.3 percent in 2020 and expected to rebound by only 0.6 percent in 2021. The number of poor people in the region—those making less than the $5.50 per day poverty line—is expected to increase from 176 million in 2019 to a conservative estimate of 192 million people by the end of 2021. The region’s public debt is expected to rise significantly. Most notably, MENA oil importers have the highest levels of debt. As the region copes with the economic consequences of the pandemic, most countries will face tensions between short-term needs and the long-term risks of debt-financed government spending. Countries must make tough choices along the road to recovery. During the pandemic, fiscal spending is arguably best used to support vulnerable families and invest in public health—such as disease surveillance, data transparency, and vaccinations. Public health investment as a short-term response to the pandemic could also bring long-term gains. As the pandemic subsides, there are good reasons to be cautious with additional fiscal stimulus, especially for countries with high debt, poor governance, and lack of transparency. After the pandemic, economic growth remains the most sustainable way to reduce the debt-GDP ratio, and this requires much-needed deep structural reforms. Strong institutions can chart a path to recovery. Investing in testing, disease surveillance, and data transparency can reduce the economic costs of the pandemic. As the pandemic subsides, effective and transparent pandemic surveillance would help boost demand from domestic and foreign sources. Good governance in public investment decisions can raise the effectiveness of public investment. Public debt transparency can help reduce borrowing costs. Institutional reforms can be implemented with limited fiscal costs and hold the promise of boosting long-run growth.